Art and conversion : an investigation of ritual, memory and healing in the process of making art - Steyn, Sonja Gruner (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (VA)(Visual Arts))--University of Stellenbosch, 2006.